2022
DOI: 10.1111/eci.13815
|View full text |Cite
|
Sign up to set email alerts
|

Global longitudinal strain by CMR improves prognostic stratification in acute myocarditis presenting with normal LVEF

Abstract: Background Prognostic stratification of acute myocarditis (AM) presenting with normal left ventricular ejection fraction (LVEF) relies mostly on late gadolinium enhancement (LGE) characterization. Left ventricular peak global longitudinal strain (LV‐GLS) measured by feature tracking analysis might improve prognostication of AM presenting with normal LVEF. Methods Data of patients undergoing cardiac magnetic resonance (CMR) for clinically suspected AM in seven European Centres (2013–2020) were retrospectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A subclinical myocardial dysfunction assessed by GLS in patients with acute myocarditis and normal LVEF might have a prognostic value for cardiovascular adverse events [ 41 ]. Moreover, CMV infection is known to deteriorate many cardiovascular diseases, such as myocarditis, atherosclerosis, hypertension, and transplant vasculopathy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A subclinical myocardial dysfunction assessed by GLS in patients with acute myocarditis and normal LVEF might have a prognostic value for cardiovascular adverse events [ 41 ]. Moreover, CMV infection is known to deteriorate many cardiovascular diseases, such as myocarditis, atherosclerosis, hypertension, and transplant vasculopathy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with preserved ejection fraction, a recent study evaluated 108 patients with suspected AMC who did not meet the definitive criteria and showed that longitudinal strain correlated with events only in patients with late gadolinium enhancement ( 22 ). Following the same line, including only patients with preserved ejection fraction, another retrospective study showed that global longitudinal strain provided independent prognostic value over late gadolinium enhancement characterization ( 23 ). A similar finding was obtained in our study, showing LV longitudinal strain as an independent variable correlated with the patient's prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the evidence-based therapeutic approach for pericarditis unrelated to vaccination was also effective in vaccine-associated pericarditis, providing a rationale for further studies of therapy in this cohort. Myopericarditis unrelated to vaccination has a long-term benign outcome, especially in the presence of preserved global longitudinal strain 21–23 . In this study, 14 most patients were only briefly admitted to hospital and responded well to standard therapy.…”
mentioning
confidence: 82%
“…Myopericarditis unrelated to vaccination has a long-term benign outcome, especially in the presence of preserved global longitudinal strain. [21][22][23] In this study, 14 most patients were only briefly admitted to hospital and responded well to standard therapy. Short-term clinical outcomes have been favourable, without relevant arrhythmias and with rapid complete recovery.…”
mentioning
confidence: 92%